Disciplined entrepreneurship startup tactics : 15 tactics to turn your business plan into a business - Cheek, Paul (Hoboken, New Jersey : John Wiley & Sons, Inc., 2024)
"For the past decade, Disciplined Entrepreneurship has changed the way people think about starting a company. Many believed that entrepreneurship could not be taught, but great entrepreneurs are not born with something special they simply make great products. Disciplined Entrepreneurship showed people how to create a successful startup through developing an innovative product by breaking down the necessary processes into an integrated, comprehensive, and proven 24-step framework that any industrious person can learn and apply. Now, Disciplined Entrepreneurship Startup Tactics provides a practical guide for securing funding and scaling your business. It's a comprehensive, practical, how-to guide for current and aspiring entrepreneurs"--Provided by publisher.
Includes index.
Keywords: Entrepreneurship; New business enterprises; Business planning